Immunopathogenesis in Myasthenia Gravis and Neuromyelitis Optica - Wang, Zhen; Yan, Yaping (Frontiers in Immunology, 2017)
Myasthenia gravis (MG) and neuromyelitis optica (NMO) are autoimmune channelopathies of the peripheral neuromuscular junction (NMJ) and central nervous system (CNS) that are mainly mediated by humoral immunity against the acetylcholine receptor (AChR) and aquaporin-4 (AQP4), respectively. The diseases share some common features, including genetic predispositions, environmental factors, the breakdown of tolerance, the collaboration of T cells and B cells, imbalances in T helper 1 (Th1)/Th2/Th17/regulatory T cells, aberrant cytokine and antibody secretion, and complement system activation. However, some aspects of the immune mechanisms are unique. Both targets (AChR and AQP4) are expressed in the periphery and CNS, but MG mainly affects the NMJ in the periphery outside of CNS, whereas NMO preferentially involves the CNS. Inflammatory cells, including B cells and macrophages, often infiltrate the thymus but not the target—muscle in MG, whereas the infiltration of inflammatory cells, mainly polymorphonuclear leukocytes and macrophages, in NMO, is always observed in the target organ—the spinal cord. A review of the common and discrepant characteristics of these two autoimmune channelopathies may expand our understanding of the pathogenic mechanism of both disorders and assist in the development of proper treatments in the future.